Meraih Kesuksesan Pendidikan: Membangun Kompetensi Pedagogik Guru Melalui Iklim Sekolah di SMK Negeri Bisnis Kota Padang - Alfin Dwi Payulan; Sulastri Sulastri (Universitas Pahlawan, 2023)
The purpose of this study is to describe the perceived school climate by teachers, the pedagogical competence of teachers, and the influence of school climate on teachers' pedagogical competence in the State Vocational High School Bisnis Kota Padang. This research is of a quantitative descriptive nature and involves 77 teachers as a sample from a population of 240 individuals. The research instrument used a questionnaire with a Likert Scale model that has been tested for validity and reliability. The results of the study indicate that the pedagogical competence of teachers in the school reaches 86.8%, while the school climate is considered conducive with an achievement level of 83.6%. Hypothesis testing shows a positive relationship between school climate and teachers' pedagogical competence. After a simple linear regression test, the equation Y = 83.25 + 0.433 X was found with a coefficient of determination of 39.8%. This indicates that 39.8% of the variability in teachers' pedagogical competence is influenced by the school climate, while other factors contribute to 60.2%.